2019
DOI: 10.1111/apa.14955
|View full text |Cite
|
Sign up to set email alerts
|

Swedish national guideline for prevention and treatment of neonatal hypoglycaemia in newborn infants with gestational age ≥35 weeks

Abstract: Aim Postnatal hypoglycaemia in newborn infants remains an important clinical problem where prolonged periods of hypoglycaemia are associated with poor neurodevelopmental outcome. The aim was to develop an evidence‐based national guideline with the purpose to optimise prevention, diagnosis and treatment of hypoglycaemia in newborn infants with a gestational age ≥35 + 0 weeks. Methods A PubMed search‐based literature review was used to find actual and applicable evidence for all incorporated recommendations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 106 publications
0
65
0
5
Order By: Relevance
“…As the ''normal'' range of blood glucose is different for each newborn and depends upon a number of factors 13 including birth weight, gestational age, availability of energy stores, feeding status, and presence or absence of disease, any hypoglycemia management must account for the overall metabolic and physiologic status of the infant, and should not unnecessarily disrupt the mother-infant relationship and breastfeeding. Several authors have suggested algorithms for screening and treatment, 2,47,48,[77][78][79] and the United Nations Children's Fund (UNICEF UK) published a monograph on how to develop a policy on the prevention and management of newborn hypoglycemia. 80 Of the multiple guidelines, algorithms, and practice frameworks available, there are few that are as clear as those from the AAP, 2 the Canadian Paediatric Society, 47 the Swedish National Guideline, 78 and the British Association of Perinatal Medicine 79 as summarized by Dr. Jane Hawdon in 2019 81 (Fig.…”
Section: Dextrose Gel Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As the ''normal'' range of blood glucose is different for each newborn and depends upon a number of factors 13 including birth weight, gestational age, availability of energy stores, feeding status, and presence or absence of disease, any hypoglycemia management must account for the overall metabolic and physiologic status of the infant, and should not unnecessarily disrupt the mother-infant relationship and breastfeeding. Several authors have suggested algorithms for screening and treatment, 2,47,48,[77][78][79] and the United Nations Children's Fund (UNICEF UK) published a monograph on how to develop a policy on the prevention and management of newborn hypoglycemia. 80 Of the multiple guidelines, algorithms, and practice frameworks available, there are few that are as clear as those from the AAP, 2 the Canadian Paediatric Society, 47 the Swedish National Guideline, 78 and the British Association of Perinatal Medicine 79 as summarized by Dr. Jane Hawdon in 2019 81 (Fig.…”
Section: Dextrose Gel Treatmentmentioning
confidence: 99%
“…Several authors have suggested algorithms for screening and treatment, 2,47,48,[77][78][79] and the United Nations Children's Fund (UNICEF UK) published a monograph on how to develop a policy on the prevention and management of newborn hypoglycemia. 80 Of the multiple guidelines, algorithms, and practice frameworks available, there are few that are as clear as those from the AAP, 2 the Canadian Paediatric Society, 47 the Swedish National Guideline, 78 and the British Association of Perinatal Medicine 79 as summarized by Dr. Jane Hawdon in 2019 81 (Fig. 1).…”
Section: Dextrose Gel Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal hypoglycaemia in newborn infants remains an important clinical problem, and prolonged periods of hypoglycaemia have been associated with poor neurodevelopmental outcomes. Wackernagel et al have developed evidence‐based Swedish national guidelines to optimise the prevention, diagnosis and treatment of hypoglycaemia in neonates born at 35 weeks of gestation or more.…”
Section: Guidelines For Preventing and Treating Neonatal Hypoglycaemimentioning
confidence: 99%
“…an important priority to prevent hypoglycemia in newborn infants [3]. Certain risk groups, including small for gestational age infants, preterm infants, and infants of diabetic mothers, are at high risk of hypoglycaemia [4].…”
Section: Introductionmentioning
confidence: 99%